2010
DOI: 10.1590/s0100-72032010001000002
|View full text |Cite
|
Sign up to set email alerts
|

Infecção cervical por papilomavírus humano: genotipagem viral e fatores de risco para lesão intraepitelial de alto grau e câncer de colo do útero

Abstract: Recife, Nordeste do Brasil. No grupo de casos (72 mulheres com lesão intraepitelial de alto grau ou carcinoma cervical) e de controles (176 mulheres com colpocitologia normal ou com alterações benignas), foram pesquisados seis genótipos virais (HPV 16, 18, 31, 33, 6 e 11) em material da ecto-e endocérvice com primers MY09/MY11. As variáveis independentes foram hierarquizadas em três níveis de determinação: distal (sociodemográficas), intermediário (comportamentais) e proximal (realização anterior de colpocito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
3
5
0
12
Order By: Relevance
“…These findings are consistent with Oliveira-Silva et al (2011), which in a study performed in Rio de Janeiro (with PCR for DNA-HPV detection in 297 HPV positive women), noted a prevalence of 28% for HPV-16, and 14.4% for HPV-18, differing by only a third from the most prevalent genotype, which was reported for HPV-45 (7.6%), and in our study was observed for HPV-33 (9.3%). However, Mendonça et al (2010) carried out a study with 248 women in the city of Recife, and also observed that the HPV-33 genotype was the third most prevalent (13.9%), a similar percentage to the present study. The high prevalence of oncogenic genotypes found in this study indicates the need for frequent monitoring, and suggests nPCR technique for DNA-HPV detection as an alternative to early identification of women at high risk for cervical cancer development.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with Oliveira-Silva et al (2011), which in a study performed in Rio de Janeiro (with PCR for DNA-HPV detection in 297 HPV positive women), noted a prevalence of 28% for HPV-16, and 14.4% for HPV-18, differing by only a third from the most prevalent genotype, which was reported for HPV-45 (7.6%), and in our study was observed for HPV-33 (9.3%). However, Mendonça et al (2010) carried out a study with 248 women in the city of Recife, and also observed that the HPV-33 genotype was the third most prevalent (13.9%), a similar percentage to the present study. The high prevalence of oncogenic genotypes found in this study indicates the need for frequent monitoring, and suggests nPCR technique for DNA-HPV detection as an alternative to early identification of women at high risk for cervical cancer development.…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicate that most of the women came from families with a low monthly income, mostly less than one to three times the minimum wage, which is consistent with studies that suggest that a low family income is an important factor in HPV pathogenesis and infection (10) .…”
Section: Discussionsupporting
confidence: 91%
“…Most of the infected women in this study had a low level of education, and previous studies support this association (8,10) ; however, there are conflicting data on the correlation between higher education levels and the risk of HPV infection.…”
Section: Discussionsupporting
confidence: 69%
“…The other 20% can progress to lesions that precede cervical cancer (2) . The relationship between HPV and carcinogenesis depends mainly on the type of virus and its persistence and integration with the host cell (3) . Currently, there are more than 200 known types of HPV, of which about 40 infect the genital tract.…”
Section: Introductionmentioning
confidence: 99%